Characteristics of the stress-induced formation of R-phase in ultrafine-grained NiTi shape memory wire - Olbricht, J. (2013)
The transformation between the cubic B2 and monoclinic B19′ phases in ultrafine-grained pseudoelastic NiTi can occur as a two-step process involving the intermediate rhombohedral R-phase. Experimental work using differential scanning calorimetry, electrical resistance measurements and transmission electron microscopy has demonstrated the formation of this intermediate phase during thermal cycling and during mechanical loading. In the present paper, complementary mechanical and thermographic results are presented which allow to further assess the character of the stress-induced R-phase formation. The transformation from B2 to R-phase is demonstrated to occur homogeneously within the gauge length rather than via advancing Lüders-type transition regions as it is the case in the localized transformation from B2 or R-phase to B19′.